2010
DOI: 10.5213/inj.2010.14.4.275
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Injury Associated with Tension-Free Vaginal Tapes-SECUR Procedure Successfully Treated by Radiological Embolization

Abstract: Various postoperative complications have been reported after the use of tension-free vaginal tapes (TVT). The transobturator approach was introduced to minimize the potential complications. The next generation of recently introduced TVT-SECUR is intended to minimize the incidence of complications. Herein we report a case of internal pudendal artery injury sustained during this procedure that was successfully treated by radiological embolization. Angiography with vessel embolization, when available, should be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…However, although in the cases of TVT-S included here major intra-operative complications are not reported, serious adverse outcomes after TVT-S procedures have been documented; there are a number of reports of significant bleeding complications requiring laparotomy [21,22]. Recently, a case of internal pudendal artery injury after a TVT-S procedure was reported, which required radiological embolization to achieve haemostasis [23]. Furthermore, a case of a retained finger pad necessitating re-exploration in theatre has been documented after a TVT-S procedure, something which is not a risk after other MUS approaches [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, although in the cases of TVT-S included here major intra-operative complications are not reported, serious adverse outcomes after TVT-S procedures have been documented; there are a number of reports of significant bleeding complications requiring laparotomy [21,22]. Recently, a case of internal pudendal artery injury after a TVT-S procedure was reported, which required radiological embolization to achieve haemostasis [23]. Furthermore, a case of a retained finger pad necessitating re-exploration in theatre has been documented after a TVT-S procedure, something which is not a risk after other MUS approaches [24].…”
Section: Discussionmentioning
confidence: 99%
“…In our series three major complications occurred in the TVT-Secur group, and other authors have reported bladder perforation, bleeding from the corona mortis, severe bleeding from the internal obturator muscle, injury of the internal pudendal artery and even male dyspareunia [12,[36][37][38][39]. Our results indicate that despite the manufacturer's recommendation not to perform a urethrocystoscopy following an obturator membrane-anchored TVT-Secur procedure, peroperative bladder and urethral perforation should be ruled out.…”
Section: Discussionmentioning
confidence: 55%
“…The patient was in fair general health postoperative- sis in arterial injuries following synthetic MUSs [5][6][7][8][9][10][11][12][13]. Unlike previous cases, the present postoperative course was greatly protracted due to persistent infection, multiple assessments and ultimately, removal of the hematoma.…”
Section: Case Reportmentioning
confidence: 77%
“…In the last decade; embolization has gained favor for the treatment of acute hemorrhage in different anatomical areas within several surgical specialisms for the treatment of acute hemorrhage [4]. Case reports have shown favorable outcomes of arterial embolization following insertion of a synthetic Midurethral Sling (MUS) complicated by arterial hemorrhage [5][6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%